Child Crimes Through Artificial Intelligence and Ways to Overcome Them - AlAmeri, Alyazia; Alomosh, Ahmad (Al-Adab Journal, 2025)
This study aims to identify children's crimes through artificial intelligence and ways to overcome  them  through: Images of children’s crimes through artificial intelligence, the traits and characteristics of children who commit crimes through artificial intelligence, the negative effects left by children’s crimes through artificial intelligence, and the ways and means through which children’s crimes through artificial intelligence can be overcome through the use of the analytical approach. The study concluded important results about child crimes through artificial intelligence and ways to overcome them. The most prominent of these was the spread of child crimes that came as a result of the large and increasing expansion of modern artificial intelligence technologies and the diversity of different forms of artificial intelligence crimes as a result of the multiplicity of technological applications developed in the manufacture of artificial intelligence programs and the seriousness of technology crimes. Artificial intelligence has now become greater than its benefits, especially without the presence of oversight and laws to secure the manufacture of artificial intelligence systems programs.